The impacts of excess cash holdings on the value of constrained- and unconstrained- firms: Evidence from Vietnamese listed firms during the 2008 financial crisis - Tran, Huong Ngoc Thien (My University, 2018)
This paper investigates the effects of excess cash holdings on firm value of Vietnamese firms in the conditions of financial constraints and financial crisis. Using a sample of 462 non-financial listed firms on the two largest stock exchanges in Vietnam during the period of eight years (2008-2015), this paper uses the Instrumental variables regression to estimate the expected change in cash holdings. After that, the OLS regression is applied to the baseline model. It is recognized that excess cash is more valuable to constrained firms than unconstrained firms in crisis time (from 2008 to 2010). However, Vietnamese shareholders would diminish the firm value if firms accumulate more cash in hand during the 2008 crisis. Furthermore, this study finds no clear evidence about the impacts of crisis to the two subsamples of constraints when considering the volatility of excess cash holdings and firm value. Specifically, under Kaplan and Zingales (KZ) index, the crisis effects are statistically insignificant in both constrained and unconstrained groups. Under Hadlock & Pierce (HP) index, financial crisis causes a positive effects to unconstrained firms suggesting that investors place a higher value of firm performance on each additional dollar of cash holding in time of crisis than in the post-crisis time. This finding is consistent under Whited and Wu (WW) index.
Keywords: Excess cash holdings; firm value; financial constraints; financial crisis; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Master's Degree Programme in Finance|